2017
DOI: 10.2147/ott.s136840
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin inhibits epithelial–mesenchymal transition, decreases invasiveness and metastasis, and reverses IL-6 induced epithelial–mesenchymal transition, expression of MMP by inhibiting STAT3 signaling in pancreatic cancer cells

Abstract: Quercetin, a flavone, is multifaceted, having anti-oxidative, anti-inflammatory, and anticancer properties. In the present study, we explored the effects of quercetin on the epithelial–mesenchymal transition (EMT) and invasion of pancreatic cancer cells and the underlying mechanisms. We noted that quercetin exerted pronounced inhibitory effects in PANC-1 and PATU-8988 cells. Moreover, quercetin inhibited EMT and decreased the secretion of matrix metalloproteinase (MMP). Meanwhile, we determined the activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 44 publications
2
65
0
Order By: Relevance
“…20 It is also testified that the effect of QE is against F I G U R E 6 The underlying mechanism of the antitumor effect of QE the biological activity of migration and invasion by inhibiting STAT3. 16,18 At the same time, our results showed that QE could remit the changes brought by IL-6.Thus, we confirmed that QE could reverse the changes caused by STAT3 activation ( Figure 6). In accordance with expectations, we came to a conclusion, that is, the antitumor effect of QE was at least depending on its abrogation of the JAK2/STAT3 pathway.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…20 It is also testified that the effect of QE is against F I G U R E 6 The underlying mechanism of the antitumor effect of QE the biological activity of migration and invasion by inhibiting STAT3. 16,18 At the same time, our results showed that QE could remit the changes brought by IL-6.Thus, we confirmed that QE could reverse the changes caused by STAT3 activation ( Figure 6). In accordance with expectations, we came to a conclusion, that is, the antitumor effect of QE was at least depending on its abrogation of the JAK2/STAT3 pathway.…”
Section: Discussionsupporting
confidence: 77%
“…Our previous studies have shown that quercetin could protect the liver from concanavalin A‐induced acute hepatitis, ischemia reperfusion injury, and fibrosis . Others have reported that quercetin had effective anticancer functions in hepatocellular carcinoma and this function may have a close relationship with the STAT3 pathway . As a cytokine, the transcription factor STAT3, has been testified that it is closely associated with tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…The other compound, quercetin, is a flavonoid widely distributed in fruits, vegetables, and beverages that shows antioxidative, anti inflammatory, and anticancer properties. Quercetin reversed IL‐6‐induced EMT in pancreatic cancer cells through STAT3 . Collectively, the data indicate that the use of compounds targeting STAT3 might be an effective approach for curing fibrosis and cancer.…”
Section: Small Molecules Against Emtmentioning
confidence: 99%
“…Quercetin reversed IL-6-induced EMT in pancreatic cancer cells through STAT3. 44 Collectively, the data indicate that the use of compounds targeting STAT3 might be an effective approach for curing fibrosis and cancer.…”
mentioning
confidence: 99%
“…6 More important, quercetin inhibited EMT along with reduction in the secretion of MMPs. 6 More important, quercetin inhibited EMT along with reduction in the secretion of MMPs.…”
Section: Jak-stat3mentioning
confidence: 99%